PENGARUH MODEL PEMBELAJARAN DAN GAYA KOGNITIF TERHADAP KEMAMPUAN MENULIS TEKS PUISI (Studi Eksperimen pada Siswa Kelas X SMA Negeri 2 Lahat) - Yulia Nova; Johanes Sapri (UNIB Press, 2020)
Theresearchaimstodescribethedifferencesintheabilitytowritepoetry texts between students whostudywith freeinquirylearningmodels and guided inquiry,betweenstudentswhohave independentfieldcognitivefieldswithdependent fields, describe theeffect ofinteractions betweenlearningmodels and cognitive stylesontheabilitytowritepoetry text,differencesintheabilitytowritepoetry texts betweenstudentswho haveindependentfieldcognitivestyleswhostudy withfree inquiry modelswithguidedinquiry,andsodostudentswhohavefielddependent cognitivestyles.Thisstudy useda2x2factorialdesignexperimentalmethod.The studypopulation was all students of class X MIPA SMA Negeri 2 Lahat. The experimentalsampleconsistedoftwoclasses,namely classXMIPA4asan experimentalclassandX MIPA 1asa controlclass, eachof whichamounted to36 students.Datacollectioninstrumentsare performance testsandGEFTtests. Hypothesistestingusestwo-wayanalysisofvariance(Anava).Theresultsshowed that(1)Theability towritepoetry textofstudentswithafreeinquiry learningmodel isnodifferentfromguidedinquiry.(2)Theability towritepoetrytextinindependent fieldcognitivestyleishigherthanfielddependent.(3)There isaninteractioneffect betweenthelearning modelandcognitivestyle ontheabilitytowritepoetrytexts.(4) Theabilitytowritepoetrytextin thefieldofindependentcognitivestylestudentsand givenafreeinquirymodelishigherthanguidedinquiry.(5)Theabilitytowrite poetrytextsofstudentswhohaveafielddependentcognitivestyleandaregivena freeinquirylearningmodel arenot different fromguided inquiry.